Impact of work function on the resistive switching characteristics of M/ZnO/CeO2/Pt devices. (16th May 2017) - Jabeen, Shazia; Ismail, Muhammad; Rana, Anwar Manzoor; Ahmed, Ejaz
Abstract: The impact of work function difference between various top electrodes (TaN, TiN, Ti and Ni) and Pt as bottom electrode has been investigated on the resistive switching characteristics of double oxide ZnO/CeO2 RRAM films. All devices exhibited typical bipolar switching behaviour. The effect of Gibbs free energy of oxide formation as well as electronegativity of the top electrode material has also been reflected. It is noticed that a decrease in operational voltages takes place on increasing the work function difference between top (TE) and bottom electrodes (BE). In addition, interface between TE and oxide layer (ZnO) is also expected to influence resistive switching phenomenon. Devices with TaN TE showed best cycle-to-cycle uniformity in switching parameters such as SET/RESET voltages and HRS/LRS resistances and good endurance property for greater than 1000 cycles and long term stability >10 5 s.